Eastern India Collaboration on Multisystem Inflammatory Syndrome in Children (EICOMISC): A Multicenter Observational Study of 134 Cases - Nayak, Snehamayee; Panda, Prakash Chandra; Biswal, Basudev; Agarwalla, Sunil Kumar; Satapathy, Amit Kumar; Jena, Pradeep Kumar; Gulla, Krishna Mohan; Rath, Debasmita; Mahapatra, Anuspandana; Mishra, Pravakar; Priyadarshini, Debashree; Mahapatro, Samarendra; et al. (Frontiers in Pediatrics, 2022)
Background: Few single centre studies from resource-poor settings have reported about the epidemiology, clinical feature and outcome of multisystem inflammatory syndrome in children (MIS-C). However, larger data from multi-centre studies on the same is lacking including from Indian setting. Methods: This retrospective collaborative study constituted of data collected on MIS-C from five tertiary care teaching hospitals from Eastern India. Children ≤15 years of age with MIS-C as per the WHO criteria were included. Primary outcome was mortality. Results: A total of 134 MIS-C cases were included (median age, 84 months; males constituted 66.7%). Fever was a universal finding. Rash was present in 40%, and conjunctivitis in 71% cases. Gastro-intestinal and respiratory symptoms were observed in 50.7% and 39.6% cases, respectively. Co-morbidity was present in 23.9% cases. Shock at admission was noted in 35%, and 27.38% required mechanical ventilation. Fifteen (11.2%) children died. The coronary abnormalities got normalized during follow-up in all except in one child. Initial choice of immunomodulation had no effect on the outcomes. Presence of underlying co-morbidity, lymphopenia, thrombocytosis, hyponatremia, increased LDH (>300 U/L), and hypoalbuminemia were the factors significantly associated an increased mortality. Conclusions: MIS-C has myriad of manifestations. Underlying co-morbidity, lymphopenia, thrombocytosis, hyponatremia, increased LDH (>300 U/L), and hypoalbuminemia were associated with an increased mortality. No difference in outcome was noted with either steroid or IVIg or both. Coronary artery abnormalities resolved in nearly all cases.